The students’ perceptions toward teacher’s way in teaching reading comprehension - Syiar Muhammad; Asnawi Muslem; Diana Fauzia Sari (Universitas Syiah Kuala, 2017)
The objective of this qualitative study was to find out students’ perceptions toward teacher’s way in reading comprehension. The subjects of this study were 28 second grade students chosen by using purposive sampling technique. The data were collected by conducting interview and distributing questionnaire which were designed based on Likert Scale. The data of questionnaire were analyzed by using formula suggested by Sudijono (2010). The result of this study showed that most students gave positive response toward teacher’s way in teaching and learning reading comprehension process. There were only 6 students who have negative response that teacher’s ways in teaching reading comprehension which can not help, motivate and attract them in learning many reasons namely; they did not get explanation before the class begins, they did not aware of class properly and they were not excited in learning English. The classroom circumstances were not good that can make them not focus to study appropriately. Briefly, the teacher’s ways in teaching process can help, motivate, and attract them in learning English particularly the materials given related to their daily life and simple ways and detailed explanation that can ease the students grasping the lesson properly.